Effect of ozone on root colonization by VAM fungi and root nodulation on blackgram - M. WAJID KHAN, MADHU KULSHRESHTHA and (Indian Phytopathology, 2002)
The impact of ozone in two different concentrations (0.02-0.05-0.02 ppm) and (0.05 -0.1-0.05 ppm) for 7 h on alternate days on the plant growth (fresh and dry weights, lengths of shoot and root), yield, chlorophyll, seed protein, phosphorus and nitrogen, root colonization, spores of VAM fungus and root nodulation have been studied. Suppression in growth and other above parameters was less in symbiotic plants in comparison to non-symbiotic (uninoculated) plants. Dual inoculated blackgram plants had greater plant growth and other above parameters than single inoculated plants.